Understanding forgotten exposures towards achieving Sustainable Development Goal 3: a cross‐sectional study on herbal medicine use during pregnancy or delivery in Tanzania - Anna Tengia-Kessy; George Chombe Msalale (BMC, 2021)
Abstract Background In most of the sub-Sahara African countries, use of herbal medications is widely practiced during pregnancy or delivery for various reasons despite uncertainties on their pharmacological profiles. Use of unregistered herbal medicines has the potential of causing adverse health effects to the mother and the newborn, thus deterring achievement of Sustainable Development Goal 3, which aims to "ensure healthy lives and promote well-being for all at all ages". One of the targets is on reduction of morbidity and mortality among mothers and newborns. This study investigated use of herbal medicines and predictors of usage during pregnancy or delivery as a forgotten exposure towards understanding some of the challenges in achieving Sustainable Development Goal 3. Methods This cross-sectional quantitative study gathered information from women who delivered a live-born baby in the preceding two years. Using a two-stage-sampling technique, women attending reproductive, maternal and child health clinics in Tabora were selected and interviewed. Proportions were compared using chi-square test and Poisson regression analysis was performed to determine independent correlates of herbal medicine use. Results Of 340 recruited women, 208 [61.2 %; 95 % confidence interval: 55.4, 66.3 %] used herbal medicines during pregnancy or delivery. Major reasons for use included accelerating labour, 81 (38.9 %) and reducing labour pains, 58 (27.9 %). Women who made less than four antenatal visits had a 24 % higher adjusted prevalence ratio of using herbal medicines as compared to those who had at least four visits [adjusted prevalence ratio:1.24; 95 % confidence interval: 1.02, 1.50, p = 0.03]. Furthermore, the adjusted prevalence ratio of using herbal medicines was 35 % higher among women who were not discouraged by health care providers against their use as compared to those who were discouraged (adjusted prevalence ratio: 1.35; 95 % confidence interval: 1.13, 1.60, p = 0.01). Conclusions Use of herbal medicines during pregnancy or delivery among women in Tanzania is common. Independent predictors of herbal medicine use were number of antenatal visits and stance of maternity health care providers on their use. Comprehensive investigations on the magnitude, patterns and predictors of use of herbal medicines during pregnancy or delivery are warranted.